Fantoma angelika: ferramenta tridimensional para controle de qualidade em braquiterapia ginecológica - Maciel, Junio de Oliveira (2024)
This work addresses, from the perspective of Medical Physics, the context of radiotherapy applied to the treatment of cervical cancer, with a focus on High Dose Rate Brachytherapy (HDRBT). It is noteworthy that the country has a significant number of HDR-BT equipment, the majority of which is used to treat pelvic tumors in women, mainly cervical cancer. The use of HDR-BT involves treatment planning based on two-dimensional (2D) or three-dimensional (3D) radiographic images of patients. Although some other countries already adopt computed tomography for obtaining 3D images, in Brazil, this practice is still uncommon, highlighting a gap in the adoption of more advanced technologies for HDR-BT planning. With a view to contributing to the improvement of techniques employed in brachytherapy, this study aims to introduce a methodology for 3D planning of this therapeutic modality, which is also useful for 2D planning and quality control. For this purpose, a three-dimensional simulator object, named Angelika phantom, was developed and tested, which holds pieces of radiographic film for dosimetric evaluations. The phantom was produced with polylactic acid (PLA) in a Creality K1 3D printer, FDM - 1201010168, using the FDM printing technique. Dose maps on the phantom were obtained with radiographic film using the FilmQAPro software. The proposed methodology was tested at the Radiotherapy Department of the Instituto do Câncer do Ceará (ICC), in scenarios of brachytherapy with iridium-192 source. The accuracy of dose delivery in the uterus was analyzed in the phantom carrying nine pieces of radiographic film, with a ring-type applicator and post-loading of the source, considering the treatment prescription for cervical cancer as per ICC routine prescription. The methodology proved useful for evaluating 2D and 3D planning of HDR-BT. The dose maps obtained with the films were similar to those defined by the computerized planning and treatment delivery system. However, it was observed that the handling process of radiographic films needs improvement to avoid the introduction of nonconformities in the isodose maps that are not related to the methodology employed in treatment.